Identificação de microrganismos cultiváveis associados ao intestino de Anopheles darlingi (Diptera: Culicidae) com potencial à paratransgênese para o controle da malária - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal de Rondônia, 2017)
Microrganisms living in insects’ midgut have been isolated and identified for developing biotechnological tools to fight vector-born diseases. In this context, the mosquitoes Anopheles from different regions around the world have been studied about their midgut microbiota focused on paratransgenesis. However, information about microrganisms living in neotropical mosquitoes midgut are scarce. And, specially about Anopheles darlingi, the main malaria vector in the Brazilian Amazon, still this study, there were not any report about culturable microrganisms associated to this insect. The first step for paratransgenesis is to isolate culturable microrganisms naturally associated to the insect vector, and thus amenable to experimentation in laboratory. The objectives of this work were to isolate and to identify culturable bacteria and yeasts isolated from feces of Anopheles darlingi, the main vector of malaria in Brazil; to estimate the species richness and frequency distribution of the sampled bacteria and yeasts and to characterize and to select the sampled bacteria and yeasts isolated from feces of An. darlingi with potential for paratransgenesis. The female mosquitoes of An.darlingi were captured in two rural places of Porto Velho, Rondônia, Brasil. For improving the bacterial growth, mosquito feces were collected on LB agar medium and cultivated at 37 ºC for 24 hours, and for improving the yeast growth, mosquito feces were collected on YPD agar medium with Chloramphenicol and cultivated at 30 ºC for 48 hours. Sixty pure bacteria colonies and sixty pure yeast colonies were sampled. The isolates were preserved in -80 ºC freezer. PCR reactions with genomic DNA from each isolate were perfomed using the primers of 16S rRNA genes for bacteria and 26S and ITS for yeasts. From 60 bacterial isolates, 55 samples were identified. From 60 yeast isolates, 27 samples were identified. The fragments were sequenced with the Sanger method and the sequences with similarities above of 97% with sequences in reference database were deposited in Genbank (NCBI). For bacteria, MALDI-TOF, VITEK®2 and BBL Crystal were also used as a complementar protocols to identify the isolates. The identified bacteria fall into 8 genera, Enterobacter, Klebsiella, Cedecea, Pantoea, Serratia, Acinetobacter, Burkholderia and Staphylococcus. The identified yeast fall into 7 genera, Pseudozyma, Papiliotrema (Cryptococcus), Meyerozyma (=Pichia), Rhodotorula, Candida, Hanseniaspora and Metschnikowia. As candidates to paratransgenesis to control of malaria in An. darlingi are those bacteria belonging to the genera Pantoea and Serratia and the yeasts belonging to the genera Meyerozyma (=Pichia), Pseudozyma, Hanseniaspora and Metschnikowia.
Keywords: Microbiota de fezes; Simbiontes; Amazônia brasileira; Pantoea; Meyerozyma; Feces microbiota; Symbionts; Brazilian Amazon; CIÊNCIAS BIOLÓGICAS